2020
DOI: 10.3390/su12051721
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change Adaptation Measures for Buildings—A Scoping Review

Abstract: As the climate changes globally and locally, the built environment will be subject to different climatic exposure than in the past. Adaptation measures are required to ensure the long-term integrity and successful operation of the built environment. This study examines literature on climate adaptation measures for buildings through a scoping literature review. It is centered around the main journals in the field of climate adaptation of the built environment, then expanded to map the extent of scientific publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(34 citation statements)
references
References 72 publications
0
34
0
Order By: Relevance
“…The durability and life-cycle of buildings highly depend on the material properties and environmental conditions regarding their long-term performance [39]. This takes even more importance when observing the climate changes and their impact on the built environment [40,41]. Several studies already focus on the effect of these materials on the surface temperature of buildings envelopes, especially in the summer season where their positive effect is more obvious.…”
Section: Introductionmentioning
confidence: 99%
“…The durability and life-cycle of buildings highly depend on the material properties and environmental conditions regarding their long-term performance [39]. This takes even more importance when observing the climate changes and their impact on the built environment [40,41]. Several studies already focus on the effect of these materials on the surface temperature of buildings envelopes, especially in the summer season where their positive effect is more obvious.…”
Section: Introductionmentioning
confidence: 99%
“…Recent trends in revitalization policies take into account the need to apply naturebased solutions [70][71][72][73][74][75][76][77][78], as critical components of sustainability transitions [71], climate change mitigation, and adaptation strategies [79][80][81][82][83][84], important also for small municipalities [85][86][87][88][89][90]. The benefits of nature-based solutions are still not recognized enough in urban planning policies of cities [74].…”
Section: Literature Review 21 Revitalization Of Small Towns and Thementioning
confidence: 99%
“…Hauge et al [89] found that numerous user guides exist to prepare societies for the coming climate challenges, but none of the user guides describes decision processes in depth, and target groups are not specified. Stagrum et al [90] found little research on the consequences of climate change on buildings in cold regions. The majority of the identified literature concerns climate change impacts on buildings in warm climates, with overheating being seen as the greatest challenge.…”
Section: Knowledge Gapmentioning
confidence: 99%